2020
DOI: 10.1590/0102.3772e3632
|View full text |Cite
|
Sign up to set email alerts
|

Positive Education: Innovation in Educational Interventions Based on Positive Psychology

Abstract: School is configured as a social space that can essentially contribute to cognitive and emotional evolvement. Furthermore, it emerges as an important resource for Positive Psychology. This review aimed to evaluate studies that present interventions based on Positive Education. Databases searched were MEDLINE, LILACS, Psycinfo, SciELO, and Scopus, using the terms "Positive Education" and "Intervention". The study's analysis was descriptive, and the characteristics of the interventions were reported. Fourteen st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 23 publications
1
4
0
8
Order By: Relevance
“…A Positive Experiences at School Scale e a Social Emotional Health Scale-Elementary foram desenvolvidas especificamente para avaliar pontos fortes de crianças no contexto escolar, possivelmente porque a as escolas, alinhadas com as perspectivas da psicologia positiva, são instituições que serviriam como veículos do melhor desenvolvimento humano (Alzina & Paniello, 2017;Schiavon et al, 2020). Esses dois instrumentos não avaliam as 24 forças de caráter, apenas algumas que são mais presentes em crianças do que em adultos, como a vitalidade e o otimismo (Park & Peterson, 2006).…”
Section: Discussionunclassified
See 3 more Smart Citations
“…A Positive Experiences at School Scale e a Social Emotional Health Scale-Elementary foram desenvolvidas especificamente para avaliar pontos fortes de crianças no contexto escolar, possivelmente porque a as escolas, alinhadas com as perspectivas da psicologia positiva, são instituições que serviriam como veículos do melhor desenvolvimento humano (Alzina & Paniello, 2017;Schiavon et al, 2020). Esses dois instrumentos não avaliam as 24 forças de caráter, apenas algumas que são mais presentes em crianças do que em adultos, como a vitalidade e o otimismo (Park & Peterson, 2006).…”
Section: Discussionunclassified
“…As medidas de avaliação com um viés negativo, ou seja, com ênfase excessiva nos déficits ou patologias infantis, sem considerar as características boas e fortes, podem prejudicar o processo de avaliação, enquadrando-as em tratamentos que rotulam e que não lhes permitem melhorar em suas dificuldades (Brazeau et al, 2012;Reppold & Almeida, 2019). Como forma de proporcionar uma avaliação mais ampla, os pontos fortes e bem desenvolvidos de crianças passaram a ser considerados, sobretudo no contexto escolar (Furlong, You, Renshaw, O'Malley, & Rebelez, 2013;Reppold et al, 2019;Schiavon, Teixeira, Gurgel, Magalhães, & Reppold, 2020) e na preservação da saúde (Guse & Eracleous, 2011).…”
Section: Introductionunclassified
See 2 more Smart Citations
“…In turn, Parra et al (2009) explained that programs in other formats such as those described here, namely, after-school positive development programs, can also be useful resources for taking advantage of adolescents' free time, based on constructive leisure for the acquisition of skills and competencies for life, especially in vulnerable populations. In another instance, Schiavon et al (2020) consider that educational institutions are collective spaces that should provide opportunities and resources for academic learning as well as work on the mental health and well-being of their teachers and students. In fact, these authors carried out a systematic review that indicated that there is interesting correlative evidence of interventions applied to education and based on positive psychology, but that there is still a long way to go.…”
Section: Tablementioning
confidence: 99%